2015
DOI: 10.11138/jts/2015.3.4.173
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unstable osteochondritis dissecans in adults with autogenous osteochondral grafts (Mosaicplasty): long-term results

Abstract: Purpose: the unstable osteochondritis dissecans (oCD-type ii and iii according to the iCRs classification) of the knee largher than > 2.5 cm 2 in adults are uncommon lesions and there is no consensus on how to treat them. Medium-term studies have reported good re sults using autogenous osteochondral plugs (mosaicplasty). the aim of this study is to analyze the long-term results of this technique for the treatment of unstable oCD in a selected group of adult patients. Methods: four patients with oCD at either o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Among these, arthroscopic matrix‐assisted autologous chondrocyte transplantation (MACT) with an associated bone grafting procedure has been introduced aiming at overcoming the drawbacks of first‐generation ACI [11, 26, 27, 36]. In fact, MACT can be implanted with an arthroscopic approach and was shown to reduce graft hypertrophy [35], with scaffolds providing support for cell adhesion and proliferation, maintaining chondrocyte phenotype and matrix production, and avoiding the dedifferentiation into fibroblasts typical of 2D culture [18, 29]. This technique showed promising results at mid‐term follow‐up [17], but no long‐term data are available, yet.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, arthroscopic matrix‐assisted autologous chondrocyte transplantation (MACT) with an associated bone grafting procedure has been introduced aiming at overcoming the drawbacks of first‐generation ACI [11, 26, 27, 36]. In fact, MACT can be implanted with an arthroscopic approach and was shown to reduce graft hypertrophy [35], with scaffolds providing support for cell adhesion and proliferation, maintaining chondrocyte phenotype and matrix production, and avoiding the dedifferentiation into fibroblasts typical of 2D culture [18, 29]. This technique showed promising results at mid‐term follow‐up [17], but no long‐term data are available, yet.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the long-term clinical outcome after mosaicplasty varies greatly depending on age, gender, and the size of the lesion [31,47,51,54,[57][58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while Smolders et al [54] described satisfactory results treating OCD lesions ranging from 0.5 to 3.2 cm 2 , and other studies reported that OAT provides good-to-excellent results when applied to smaller articular cartilage between 1 and 4 cm 2 [58], lesions > 6 cm 2 are associated with a poor prognosis, even when multiple graft plugs are used [53]. Furthermore, few studies with small cohorts have looked specifically at the use of OAT for the treatment of OCD [32,54,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%